Pengolahan Minuman Berkhasiat dari Tanaman Obat Keluarga (Toga) untuk Peningkatan Kesehatan dan Keterampilan Bisnis di Desa Denggungan, Boyolali - Ramadhan, Ana Noviana; Qolby, Fatihatul; Faradina, Tazky Aulia; Putri, Hanan Aliya; Amalia, Prita; Maulanisa, Hasna Fitri; Hayati, Aisyah Nur; Irawan, Fery; Astuti, Violi Maulidya Charlieans Ning; Aziz, Wahyu Rizkika; Suswardany, Dwi Linna (Academia Publication, 2023)
Tanaman Obat Keluarga (TOGA), also known as live medicinal plants, are plants planted in the home yard. Based on data from the 2022 Boyolali Regency Health Profile, the prevalence of sufferers of degenerative diseases such as hypertension in Boyolali Regency is 38.63% or 199,370 people. Meanwhile, the prevalence of diabetes mellitus (DM) was 2.2% or 18,325 people. This service is carried out with the aim of building and implementing community habits in consuming healthy drinks made from TOGA spices in order to prevent degenerative diseases in society. This activity takes place in several activity stages, namely 1) Preparation stage, 2) Implementation stage which consists of material socialization, product demonstrations, cooking practices and business materials, 3) Evaluation. It is hoped that the sustainability of this program can be carried out by utilizing home gardens as land for planting TOGA, so that the use of TOGA for health can be carried out sustainably and have an impact on the socio-economic aspects of the community.